Are New Career Models for Science Research Emerging? (International Journal of Gender, Science and Technology, 2018)
This paper explores how the traditional gendered model of science excellence impacts on the careers of women scientists. Using an Australian case study, it then examines the following aspects of science careers:& what gives scientists job satisfaction; differing perceptions of how to build science careers; how networks, mobility and mentoring are fundamental to research careers; how gender is often a factor in science research careers; and huge generational change underway that is leading to new career models.& The paper argues that these new models have the capacity to change the traditional gendered model of science careers.